Cyberfeminism in Public Sphere: Descriptive Studies on Female Daily Network through FD TALK Feature - Nadya Poernamasari (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2023)
The presence from application user generated content like Female Daily Network become a place to build relations between women in the world of cyberfeminism online. New media with a variety of conveniences offered to each user in order to obtain information and solve problems related to certain issues, among others; beauty, health, lifestyle, information, and recommendations. Through the linkage of new media and public sphere as a forum for interaction and socialization, this research focuses on describing how community activities in Female Daily Network through the FDApp. Cyberfeminism perspective used in an effort to facilitate the interaction of female users in the FD Talk feature. This study uses a qualitative descriptive method, with primary data in the form of indirect observation and secondary data in the form of documentation and literature studies. Activity of women support women as a form cyberfeminism with several groups that have a high level of activity. Not just focus on the group beauty, but also in mental health, and occupational groups. User personalization on Female Daily, freedom of opinion, and the involvement of all users in interactions and discussions are real manifestations of an egalitarian, free from domination, and inclusive public sphere.